Analisis Variasi Metode Perawatan Pada High Volume Fly Ash Concretemutu Tinggi Terhadap Sifat Mekanisnya - Romadhoni, Nurnaim, Mochamad Solikin, S.T., M.T., Ph.D (2016)
Concrete care is a process that aims to keep the concrete is not too rapid loss of water, keeping moisture or concrete. This research was conducted at high volume fly ash concrete with concrete quality planned f'c 45 MPa, using a mix design method of ACI, the value of the planned slump 10 ± 2 cm. Tests conducted in this study is the compressive strength, tensile strength sides and water uptake. Prior to testing, concrete treated by immersion for 28 days and 56 days, was treated in a manner flush and in closed sacks for 14 days. Results of testing the compressive strength of concrete at 28 days and 56 days with treatment soaked, high-volume fly ash concrete compressive strength value of 31.61 MPa 28 days and 58.32 MPa age of 56 days, higher than the normal concrete (without fly ash) is aged 28 days to 31.05 MPa and 50.20 MPa. At high volume fly ash concrete aged 28 days and 56 days with care watered compressive strength value of 20.85 MPa 28 days and 45.48 MPa age of 56 days, and in the care of closed sack compressive strength value of 25.57 MPa age 28 day and 47.28 MPa age of 56 days. Testing the tensile strength divided on concrete High Volume Fly Ash age of 56 days with treatment soaked ie 11.793 MPa higher than normal concrete (without fly ash) amounted to 10.889 MPa, benton High Volume Fly Ash curing flush amounted to 9.022 MPa, curing lid sacks 8.148 MPa. And of testing the water uptake in normal concrete (without fly ash) 2.833%, concrete HVFA of 2.790%, 3.575% flush with the care and treatment of closed sacks 3.135%. The compressive strength and tensile strength sides of high volume fly ash concrete soaked care is higher than in the treatment of flushing and closed sack. And the absorption of high volume fly ash concrete with deep soaking treatment at less than the watered treatments and closed the sack